Two Sides of the Same Coin? : Rebalancing and Inclusive Growth in China - Lee, Il (IMF Working Papers; Working Paper, 2013)
This paper uses the Shapley Value decomposition technique to assess the factors behind the rise of inequality in China. It finds that, in many ways, inequality may have been an inevitable by-product of China's investment and export-led growth model. Between Chinese households, we find that the most important factors explaining income inequality are location, education, access to health insurance, and labor market variables, including the sector of employment and enterprise size. Across China's provinces, divergences in per capita incomes are driven by the relative level of capital-intensity, public spending, financial access, privatization, and urbanization. In addition, excess liquidity may have exacerbated inequality in the last decade, by driving up property prices and the wealth gap. Based on these results, policies that could help broaden the benefits of growth in China include maintaining prudent monetary and credit policies, a more progressive fiscal tax and expenditure system, higher public spending on health and education, deregulation and reforms to increase competition, measures to raise labor incomes and assist vulnerable workers, and better access to finance for both households and SMEs, including in rural areas. Not surprisingly, given the argued nexus between China's growth strategy and inequality, many of these reforms are the same ones that would help rebalance its economy toward consumption and household incomes.